Six characters in search of an author - Pirandello, Luigi, 1867-1936 (Italica Press, 2013)
Presented here for the first time together, and many for the first time in English, are the writings that formed the genesis of Six Characters in Search of an Author, along with a new translation of the theater masterpiece itself. The idea of characters as living beings in dialogue with their author first appears as a major theme in a previously-untranslated short story titled ""Characters."" The interaction between characters demanding to ""live"" in writing and an author who rejects them would be developed in Pirandello's 1911 story ""The Tragedy of a Character."" In 1925, Pirandello conceiv.